(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Innovation affects the transformation of organizational characteristicsor organizational behavior. In addition, the food industry is an important part of Thailand’s economic and social system because it is a connected industry. With many consecutive industries and incomes, GDP ranks first. The purpose of this study is to study the marketing innovation factors that affect competitive advantage Innovation diffusion theory. The sample was a targeted population of the food and beverage sector, and 400 samples of SMEs in Bangkok and metropolitan areas were found.The results of the exploratory factor analysis of the parameters of marketing innovation and competitiveness passed the minimum threshold of not less than 0.50, consistent with the corroborative confirmatory factor analysis. When analyzing the causal influence between the latent external variables of marketing innovation and the latent variables in the competitiveness, they were found to have a component weight of 0.31 and a t-test value of 5.25, there was statistically significant. Suggestions for research and development of marketing innovations such as promoting marketing through social media Promotion of new marketing, including creating more innovative products to create added value. as well as packaging that can add value and attract the attention of consumers. The important thing is to develop products that are suitable for consumers in each age. New knowledge found that small and medium-sized community enterprise entrepreneurs found that they had created innovations by developing traditional marketing channels and through social media, including the development of standardized product quality.